Characterization of nonOhmic electrical transport in double perovskite compounds through bias scale and nonlinearity exponent. (January 2017) - Chakraborty, D.; Nandi, U.N.; Jana, D.; Dasgupta, P.; Poddar, A.
Abstract: Scaling analysis of nonOhmic electrical transport in double perovskite (DP) compounds like La2 NiMnO6 and Sr2 Fe0.3 Mn0.7 MoO6 is presented over a wide range of electric bias and temperatures. It is shown that the voltage V 0 ( T ) at which conductance deviates from its Ohmic value Σ 0 ( T ) scales with Σ 0 ( T ) as V 0 ( T ) ∼ Σ 0 ( T ) x T, x T being the onset exponent characterizing the onset of nonOhmic conduction. Interestingly, it was found that x T is negative and insensitive to the nature of conduction mechanism in DPs but is related to the characteristic temperature T 0 and the mean hopping length H m . We provide a scaling formalism in terms of the parameters V 0 ( T ) and x T in DPs for deeper understanding of the spintronic application and the electrode functioning in solid oxide fuel cells (SOFC). Inelastic multi-step tunneling is found to be the suitable mechanism of electronic transport characterized completely by these two parameters.